2006
DOI: 10.1117/12.692886
|View full text |Cite
|
Sign up to set email alerts
|

NIL template making and imprint evaluation

Abstract: Nano-imprint lithography (NIL) is expected as one of the candidates for hp32nm to hp22nm technology nodes. NIL needs 1X patterns on masks and a transit from 4X to 1X means a big and hard technology jump for the mask industry. We have reported in previous papers 1,2,3 that the resolution limit with 50keV acceleration voltage VSB (variable shaped beam) electron beam writer, which are used in current 4X photomask manufacturing, was around 65nm. And we have also reported that to reach the required resolution for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The 100kV-SB writer gives higher resolution. 1,2 Figure 2 is cross sectional SEM images of resist patterns with a half pitch (hp) of 22, 24, and 26nm. 3 These fine features are realized by a combination of a 100kV-SB writer and a non-CAR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 100kV-SB writer gives higher resolution. 1,2 Figure 2 is cross sectional SEM images of resist patterns with a half pitch (hp) of 22, 24, and 26nm. 3 These fine features are realized by a combination of a 100kV-SB writer and a non-CAR.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 1 and 2 show some results on 1X patterning. [1][2][3] Figure 1 is SEM images of resist and etched quartz, the patterns of which are delineated by a 100kV-SB (spot beam) EB writer, and SEM images of etched quartz obtained with a 50kV-VSB writer. The 100kV-SB writer gives higher resolution.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying about the possibility of practical template fabrication and although it is difficult to apply the technology for full-chip pattern making because of the low speed, we have been using a 100kV spot beam writer for the pattern generation and a non-CAR resist [1][2][3][4] . Our trial against faster pattern writing will be reported and discussed in another paper at this symposium 5 .…”
Section: Introductionmentioning
confidence: 99%